2023
DOI: 10.1002/anie.202314523
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Electron Delocalization in Vanadium‐Based Hybrid Bronzes through Molecular Templation

Suchen Wan,
Nicole Musielak,
Allen G. Oliver
et al.

Abstract: We show that the conductivity of hybrid vanadium bronzes—mixed‐valence organic‐inorganic vanadium oxides—can be tuned over six orders of magnitude through judicious choice of molecular component. By systematically varying the steric profile, charge density, and propensity to hydrogen bond across a series of eight diammonium‐based molecules, we engender multiple distinct motifs of V–O connectivity within the two‐dimensional vanadium oxide layers of a family of bulk crystalline hybrid materials. A combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…In contrast to these glass samples, the 30HO 1/2 –6VO 5/2 –14VO 2 –50PO 5/2 glass reported herein is unusual because it contains numerous VO 6 units whose role is not clearly known. Recently, the electronic conductivity of various hybrid vanadium bronzes was found to vary widely and be extremely sensitive to the atomic configuration around the V atoms and the connectivity of vanadium oxide polyhedra . Therefore, the greatly different role of VO 6 and VO 4 on electrical conduction in glass is highly plausible.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to these glass samples, the 30HO 1/2 –6VO 5/2 –14VO 2 –50PO 5/2 glass reported herein is unusual because it contains numerous VO 6 units whose role is not clearly known. Recently, the electronic conductivity of various hybrid vanadium bronzes was found to vary widely and be extremely sensitive to the atomic configuration around the V atoms and the connectivity of vanadium oxide polyhedra . Therefore, the greatly different role of VO 6 and VO 4 on electrical conduction in glass is highly plausible.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Raman spectrum did not provide information on the valence state and coordination number of V ions, although some reports have ascertained the coordination number from Raman spectra. Therefore, in the present study, the structures of the glass samples were explored by referring to previously reported 31 P and 51 V nuclear magnetic resonance (NMR) spectra of glass samples with nominal compositions close to that of the 30NaO 47 among these samples, the glass sample with x = 10 is similar in composition to the glass reported herein. According to their report, the phosphate framework comprised Q 2 units with a considerable amount of Q 1 ; notably, their NMR results substantiate the aforementioned explanation of the Raman spectra of the glass investigated herein.…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation